Antihypertensive and vasorelaxant effects of aqueous extract of Artemisia campestris L. from Eastern Morocco. (12th July 2017) - Dib, Ikram; Tits, Monique; Angenot, Luc; Wauters, Jean Noel; Assaidi, Asmae; Mekhfi, Hassane; Aziz, Mohammed; Bnouham, Mohammed; Legssyer, Abdelkhaleq; Frederich, Michel; Ziyyat, Abderrahim
Abstract: Ethnopharmacological relevance: Artemisia campestris L. (Asteraceae) has many traditional uses, among which treatment of diabetes and hypertension. Aim of the study: This study was conducted in order to confirm the antihypertensive and hypotensive effects of A. campestris L. aqueous extract (AcAE) and to explore the underlying mechanism of action of its vasorelaxant effect, besides the acute toxicity. Also, the chemical composition of AcAE was investigated. Material and methods: the chemical content of AcAE was determined by using HPLC and NMR techniques. The antihypertensive effect was assessed indirectly by tail-cuff method on L-NAME induced hypertensive rats, while the hypotensive action was monitored intravenously by invasive method on normotensive rats. The vasorelaxant effect and vascular mechanism of action were studied in the presence of antagonists and blockers on aorta isolated from normotensive rats. On the other side, the acute toxicity was studied by oral feeding of extract to the mice. Results: The global phytochemical profile of AcAE reveals the presence of several polyphenols as main components. A. campestris L. infusion was characterized by mono- and di-cinnamoyl compounds, with 3, 5-dicaffeoylquinic (isochlorogenic A) acid being the main compound, followed by 5-caffeoylquinic (chlorogenic) acid. Vicenin-2 (apigenin 6, 8-di-C-glucoside) appeared to be the most abundant compound among flavonoids. The daily treatment with AcAE at 150 mg/kg/day prevented the installation of hypertension on L-NAME hypertensive rats, and reduced SBP from 172 mmHg up to 144 mmHg. At the dose 40 mg/kg, AcAE provoked reduction of systolic (SBP), diastolic (DBP) and mean arterial pressure (MAP), without affecting the heart rate. Also, AcAE (10 −2 −2 mg/ml) relaxed the precontracted aorta by 95.8±1.3%. The denudation and preincubation of aorta with atropine, calmidazolium, L-NAME, hydroxycobalamin, ODQ, 8-RP-Br-PET-cGMP, thapsigargin and verapamil attenuated the vasorelaxant response, while the pre-treatment with 4-AP, TEA, glibenclamide and BaCl2 did not alter this effect. The oral administration of AcAE (0–6 g/kg) reveals no mortality or toxicity. Conclusions: our study proved that AcAE possess an important antihypertensive, hypotensive and vasorelaxant effect, which is mediated via calmodulin-NO-cGC-PKG pathway, and via inhibition of calcium influx through voltage-operated calcium channels and activation of intracellular calcium mobilization into sarcoplasmic reticulum. Therefore, our findings give first evidence about the traditional use of A. campestris L. as antihypertensive plant. Graphical abstract: